Involvement of SUR2/Kir6.1 channel in the physiopathology of pulmonary arterial hypertension - Le Ribeuz, Hélène; Masson, Bastien; Dutheil, Mary; Boët, Angèle; Beauvais, Antoine; Sabourin, Jessica; De Montpreville, Vincent Thomas; Capuano, Véronique; Mercier, Olaf; Humbert, Marc; Montani, David; Antigny, Fabrice (Frontiers in Cardiovascular Medicine, 2023)
Aims We hypothesized that the ATP-sensitive K+ channels (KATP) regulatory subunit (ABCC9) contributes to PAH pathogenesis. ABCC9 gene encodes for two regulatory subunits of KATP channels: the SUR2A and SUR2B proteins. In the KATP channel, the SUR2 subunits are associated with the K+ channel Kir6.1. We investigated how the SUR2/Kir6.1 channel contributes to PAH pathogenesis and its potential as a therapeutic target in PAH. Methods and results Using in vitro, ex vivo, and in vivo approaches, we analyzed the localization and expression of SUR2A, SUR2B, and Kir6.1 in the pulmonary vasculature of controls and patients with PAH as in experimental pulmonary hypertension (PH) rat models and its contribution to PAH physiopathology. Finally, we deciphered the consequences of in vivo activation of SUR2/Kir6.1 in the monocrotaline (MCT)-induced PH model. We found that SUR2A, SUR2B, and Kir6.1 were expressed in the lungs of controls and patients with PAH and MCT-induced PH rat models. Organ bath studies showed that SUR2 activation by pinacidil induced relaxation of pulmonary arterial in rats and humans. In vitro experiments on human pulmonary arterial smooth muscle cells and endothelial cells (hPASMCs and hPAECs) in controls and PAH patients showed decreased cell proliferation and migration after SUR2 activation. We demonstrated that SUR2 activation in rat right ventricular (RV) cardiomyocytes reduced RV action potential duration by patch-clamp. Chronic pinacidil administration in control rats increased heart rate without changes in hemodynamic parameters. Finally, in vivo pharmacological activation of SUR2 on MCT and Chronic-hypoxia (CH)-induced-PH rats showed improved PH. Conclusion We showed that SUR2A, SUR2B, and Kir6.1 are presented in hPASMCs and hPAECs of controls and PAH patients. In vivo SUR2 activation reduced the MCT-induced and CH-induced PH phenotype, suggesting that SUR2 activation should be considered for treating PAH.